Recent advances in single crystal narrow band-gap semiconductor nanomembranes and their flexible optoelectronic device applications: Ge, GeSn, InGaAs, and 2D materials. Issue 7 (8th February 2023) - An, Shu; Park, HyunJung; Kim, Munho
Abstract : Flexible optoelectronics have attracted much attention in recent years for their potential applications in healthcare and wearable devices. Abstract : Flexible optoelectronics have attracted much attention in recent years for their potential applications in healthcare and wearable devices. Narrow bandgap (NBG) semiconductor nanomembranes (NMs) are promising candidates for flexible near-infrared (NIR) applications due to their light weight, bendability, and excellent material properties ( e.g., fast carrier mobility and appropriate bandgap energy). However, a comprehensive summary of the current research on the NBG NMs has not been provided yet. This review highlights recent advances in the development of NBG semiconductor NMs, including Group IV ( e.g., Ge and GeSn) and III–V ( e.g., InGaAs) compounds, and 2D materials ( e.g., black phosphorus and graphene) and their applications in flexible optoelectronics. The material growth, fabrication process, and characterization of material properties are summarized. Moreover, abundant applications in flexible devices are present, including but not limited to photodetectors, light emitting diodes, and lasers.